Recovery of Green Plantlets from Albino Shoot Primordia Derived from Anther Culture of Indica Rice (Oryza sativa L.) - Abul Kashem Md. Mohiuddin; Nilufer Hye Karim; Shahanaz Sultana; Zannatul Ferdous (Tropical Life Sciences Research, 2011)
A simple method was developed to permit albino plant regeneration from anther culture of Hobigonj Boro (Hbj B) IV and Hbj B VI, two local varieties of aromatic indica rice from Bangladesh. Three crucial factors were identified for the albino shoot primordia to change into green plantlets in culture; components of M10 induction medium, callus size (range 0.2–0.4 cm long) and height of shoot primordia (range 2–3 mm). Immediate transfer of shoot primordia (2–3 mm) from M10 medium to regeneration medium followed by continuous incubation under fluorescent light (100-lux, 25±1°C) triggered albino shoot primordia to turn green in 2–3 days. Callus size did not show any effect on the change. Albino plantlets derived from anther callus cultured in KA, KB, KC, KD and KE media did not recover in both the varieties. Transfer of albino shoot primordia shorter or longer than 2–3 mm from the above 5 cultures to regeneration medium did not cause the shoot primordia to turn green. 100% albino shoot primordia initiated from Hbj B VI and 79% from Hbj B IV in M10 medium changed to green plantlets upon transfer to regeneration medium. Subsequent culture and subculture of green plantlets showed rapid formation of many new green plantlets. Suatu kaedah mudah dibangunkan yang membenarkan regenerasi tumbuhan albino daripada kultur anter Hobigonj Boro (Hbj B) IV and Hbj B VI, dua varieti tempatan padi indica beraromatik dari Bangladesh. Tiga faktor penting telah dikenalpasti untuk tunas/pucuk primordia albino untuk bertukar menjadi pucuk/tumbuhan hijau dalam kultur; komponen-komponen medium induksi M10, saiz kalus (0.2–0.4 cm panjang) dan tinggi tunas/pucuk primordia (2–3 mm). Perpindaan serta-merta tunas/pucuk primordia (2–3 mm) daripada medium M10 ke medium regenerasi diikuti dengan inkubasi berterusan di bawah lampu pendarfluor (100-lux, 25±1°C) telah mencetuskan penukaran tunas/pucuk primordia albino menjadi hijau dalam 2–3 hari. Saiz kalus tidak menunjukkan sebarang perubahan. Pucuk albino yang dihasilkan daripada kalus anter yang dikultur di dalam media KA, KB, KC, KD dan KE tidak pulih dalam kedua-dua varieti. Perpindahan pucuk primordia albino lebih pendek atau panjang dari 2–3 mm daripada kelima-lima kultur tersebut ke medium regenerasi tidak menyebabkan pucuk primordia untuk bertukar menjadi hijau. 100% pucuk primordia albino yang dihasilkan daripada Hbj B VI dan 79% daripada Hbj B IV dalam medium M10 bertukar menjadi hijau selepas dipindahkan ke medium regenerasi. Kultur seterusnya dan subkultur tumbuhan hijau menunjukkan formasi cepat pucuk hijau yang banyak.